Commercializing inventions from public research: Does speed matter? - Alexander Schacht (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
This study addresses the determinants of time-to-licensing, defined as the elapsed time between the disclosure of an invention and the signed licensing contract, and its impact on the commercial success of the licensed inventions from public research. Using a dataset containing detailed information on the licensing activities of the Max Planck Society, I do not find significant evidence that time-to-licensing negatively influences the commercial success of the inventions disclosed between 1980 and 2004. However, separating the effect of the time-to-licensing for the inventions disclosed between 1990 and 2004, I do find a significant negative influence on the likelihood and extent of the commercial success. Thus, the pace of technology transfer has become important because of the rapidly changing business environment and technological obsolescence. Furthermore, inventions from the biomedical section, collaborative inventions with private-sector firms, and inventions that are co-invented with senior scientists require less time to become licensed.
Keywords: L24; L25; O32; 330; academic inventions; innovation speed; technology commercialization; Hochschulforschung; Lizenz; Technologietransfer; Innovation; Zeit; Kommerzialisierung; Deutschland